Students’ Creative Thinking Skills on Green Chemistry by Designing Fire Reterdant Bamboo - Sausan, Saniyyah; Supriatna, Asep; Mudzakir, Ahmad l (Jurnal Pendidikan MIPA, 2022)
This study aims to reveal students' creative thinking skills through the implementation of fire-retardant bamboo learning designs using ionic liquids that integrate chemical bonding materials and polymers. This research method is qualitative research. The research was conducted in class XII of SMA N Cibinong for two meetings with 36 students. The instruments used were observation sheets and video-audio recordings. The data obtained was analyzed using the transcript based lesson analysis method to determine the profile of students' creative thinking abilities. The creative thinking indicators used are five creative thinking indicators according to Munandar (1992). The percentage of indicators of creative thinking skills that appear the most in the first and second meetings is the indicator of fluency as much as 60.1% in the first meeting and as much as 62.1%. While the indicator with the least percentage of appearances at the first and second meetings is the originality indicator of 3.2% at the first meeting and as much as 0.1% at the second meeting learning activities. Keywords: green chemistry, creative thinking skills, transcript base lesson analysis. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1759-1768